The Greek and Jewish Origins of Docetism: A New Proposal - Goldstein, R; Stroumsa, G (2007)
Despite the amount of work on Docetic trends in early Christianity, in particular in the last generations, thanks to the renewed interest in Gnosticism after the Nag Hammadi discovery, the origins of Docetism remain obscure. While various suggestions have been offered, they usually point to either to Jewish or to Greek origins of Docetic attitudes. This article offers a new model, which seeks to combine both Greek and Jewish origins. The article calls attention to the Greek conception of the eidōlon of a person (or of a divinity) taking its place under certain conditions. This conception had been systematically used in Greek classical literature in order to solve hermeneutical problems in mythology. We argue that the Greek conception of the eidōlon was combined to Jewish interpretations of Genesis 22 and of Psalm 2 in the earliest stages of Christianity in order to offer a solution to the scandal of Christ's Passion. © Walter de Gruyter 2007.